Animal Real-Unreal in Traditional Conceptions of the World in Croatian Areas - Bajuk, Lidija (Poznańskie Studia Slawistyczne, 2021)
Trying to interpret oneself and the other in the world, the traditional Man has established a real world and an otherworld. Specific herbal and animal attributes were ascribed to particular people who allegedly had the power to communicate between worldliness and transcendence. Also some human characteristics were linked with herbal and animal mediators. These attributes were folklorized as miraculous powers. Such supernatural beings from South Slavic traditional conceptions of the world have been largely associated with the pre-Christian deities and their degradations, based on the observed real attributes of the vegetal and animal species. The interdisciplinary comparative way of treating South Slavic folklore real-unreal motifs through time and space in this article is its ethnological, animalistic and anthropological contribution.